Laminated glass and head-up display systems
The laminated glass structure with specific nanofilms and layers addresses low P-polarized light reflectance and spectral smoothness issues, improving display quality and user comfort in head-up display systems.
Patent Information
- Application Number
- JP2024562220
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-17
- Filing Date
- 2023-01-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-01-17
AI Technical Summary
Conventional laminated glass used in head-up display systems has low P-polarized light reflectance and poor smoothness of the reflection spectrum, affecting the display quality and user comfort.
A laminated glass structure with an inner glass substrate, an outer glass substrate, and an intermediate film, featuring a first transparent nanofilm with alternating high and low refractive index layers, and a second transparent nanofilm with dielectric and conductive layers, enhancing P-polarized light reflectance and spectral smoothness.
Improves P-polarized light reflectance and spectral smoothness, enhancing the brightness and comfort of head-up display systems, while also increasing thermal insulation and allowing for electric heating functions.
Smart Images

Figure 2025501415000001_ABST
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority from Chinese patent application 02210047539.7 filed on January 7, 2022, and is a national phase application of international application PCT / CN2023 / 072616 filed on January 7, 2023. This application relates to the technical field of head-up displays, and in particular to laminated glass and head-up display systems. [Background technology]
[0002] Head-up display systems (HUDs) are increasingly being used in automobiles and other fields, and the installation of laminated glass is one of the key points in the design of head-up display systems.
[0003] At present, conventional laminated glass generally has a coating layer on the inner glass substrate that can reflect P-polarized light, but the high refractive index material used in the coating layer has a low refractive index, making it difficult to obtain a P-polarized light reflectance that meets the high-quality requirements for use in head-up display systems. At the same time, even the simple overlapping of two coating layers used in conventional laminated glass cannot sufficiently smooth the reflection spectrum of P-polarized light of the laminated glass, and the non-smooth reflection spectrum of P-polarized light significantly affects the display effect of the image of the projector and the driving comfort of the car using the head-up display system.
[0004] In other words, conventional laminated glass has the problem that it has a low P-polarized light reflectance and a poor smoothness of the reflection spectrum for P-polarized light. Summary of the Invention [Problem to be solved by the invention]
[0005] In response to the problems in the conventional technologies, the present application provides laminated glass and a head-up display system that can simultaneously improve the P-polarized light reflectance of laminated glass and the smoothness of the reflection spectrum due to P-polarized light, and further effectively improve the brightness and display comfort of a head-up display system that uses laminated glass, thereby meeting the needs for commercialization of laminated glass and further contributing to improving usability for users.
[0006] In order to solve the above technical problems, the present application provides the following technical solutions: [Means for solving the problem]
[0007] According to a first aspect, the present application provides a laminated glass, the laminated glass comprising an inner glass substrate, an outer glass substrate, and an intermediate film interposed between the inner glass substrate and the outer glass substrate, a first transparent nanofilm for reflecting P-polarized light is provided on one side of the inner glass substrate away from the intermediate film, the first transparent nanofilm comprises at least one laminated structure consisting of a high refractive index material layer and a low refractive index material layer deposited in order from the surface of the inner glass substrate outward, a second transparent nanofilm is interposed between the inner glass substrate and the outer glass substrate and is adhered to the intermediate film, the second transparent nanofilm comprises a dielectric layer and a conductive layer, and each of the conductive layers is interposed between two of the dielectric layers.
[0008] The high refractive index material layer has a refractive index of 1.9 or more, and the low refractive index material layer has a refractive index of 1.8 or less. The laminated glass has a P-polarized light reflectance Rp≧16% when the incident angle is 65°.
[0009] Furthermore, when the incident angle of the laminated glass is 65°, the reflection spectrum corresponding to the P-polarized light reflectance Rp is within the wavelength band of 460 nm to 630 nm.
[0010] The beneficial effects of this technical solution are that it can realize a display with as neutral a color tone as possible on the laminated glass of a projected image, without significant minimums (local minimums) and maximums (local maximums), and meets the requirements of aesthetics; it can effectively improve the neutral color degree and comfort of a head-up display system using this laminated glass, and can effectively improve the driving comfort of users.
[0011] Furthermore, the direct reflectance Rds of the laminated glass to sunlight is 20% or more.
[0012] The beneficial effects of this technical solution are that it can effectively increase the direct reflectance of sunlight on the laminated glass, effectively improve the heat insulating effect of the laminated glass, and further improve the heat insulating effect of a head-up display system using the laminated glass, thereby meeting the needs of commercialization and further contributing to improving user convenience. In addition, the second transparent nano-film includes a conductive layer and is suitable for use in electrical heating, enabling rapid dehumidification, defog, and even de-icing, so the laminated glass of the present invention may have the function of electrical heating and is very suitable for a power supply of 8V to 48V. Second transparent nanocoating When the bus bar is provided, it is connected to the electrode of the power supply and the above-mentioned is performed in as wide a part as possible of the width of the glass substrate. Second transparent nanocoating A current can be introduced into
[0013] Furthermore, the first transparent nanofilm has a one-sided P-polarized light reflectance R1p≧6% when the incident angle is 65°.
[0014] Furthermore, the first transparent nanofilm has a one-sided P-polarized light reflectance R1p≧15% when the incident angle is 65°.
[0015] The beneficial effect of the technical solution is that the higher the first transparent nanofilm, the higher the R1p / Rp ratio, thereby increasing the design freedom of the second transparent nanofilm without relying on a wedge-shaped intermediate film and / or reducing the requirements for the second transparent nanofilm.
[0016] Furthermore, the refractive index of the high refractive index material layer is 2.4 or more, and the refractive index of the low refractive index material layer is 1.6 or less.
[0017] The beneficial effect of the technical solution is that the combination of the high refractive index material layer and the low refractive index material layer can realize the requirements for the first transparent nanofilm, and at the same time, contribute to improving the appearance of the head-up display system using the laminated glass.
[0018] Furthermore, at least one of the high refractive index material layers has a thickness of 45 nm or more and a refractive index of 2.4 or more.
[0019] The beneficial effect of the technical solution is that it contributes to obtaining high smoothness of the spectrum of P-polarized light and improving the appearance of the HUD.
[0020] Furthermore, in the laminated glass, when the incident angle is 65°, the range of the reflection spectrum corresponding to the P-polarized light reflectance Rp in the wavelength band of 460 nm to 630 nm is 4% or less.
[0021] The beneficial effects of this technical solution are that it can effectively improve the smoothness of the reflection spectrum of P-polarized light of the laminated glass, and can realize the display of a projected image on the laminated glass with as neutral a color tone as possible, without significant minimum and maximum, and can further improve the neutral color development degree and comfort of a head-up display system using this laminated glass, and can effectively improve the driving comfort of users.
[0022] Furthermore, in the laminated glass, when the incident angle is 65°, the range of the reflection spectrum corresponding to the P-polarized light reflectance Rp in the wavelength band of 460 nm to 630 nm is 2% or less.
[0023] The beneficial effect of this technical solution is that it can further improve the smoothness of the reflection spectrum of P-polarized light of the laminated glass, and further realize the display of the projected image on the laminated glass with as neutral a color tone as possible, thereby meeting the needs of further commercialization.
[0024] Furthermore, when the incident angle of the first transparent nanofilm is 65°, the range of the reflection spectrum by P polarized light corresponding to the P polarized light reflectance R1p of one side in the wavelength band of 460 to 630 nm is defined as range1;
[0025] When the incident angle of the second transparent nanofilm is 65°, the range of the reflection spectrum of P-polarized light corresponding to the P-polarized light reflectance R2p on one side in the wavelength band of 460 to 630 nm is range2. │range1+range2│≦6%.
[0026] Furthermore, |range1+range2|≦3%.
[0027] The beneficial effect of this technical solution is that, even if the wavelengths corresponding to the maximum and minimum values of the P-polarized spectral reflectance of the first transparent nanofilm are completely consistent with the wavelengths corresponding to the maximum and minimum values of the P-polarized spectral reflectance of the second transparent nanofilm within the 460nm to 630nm wavelength band, the reflection spectrum of the P-polarized light of the laminated glass can be smoothed.
[0028] Furthermore, when the incident angle of the first transparent nanofilm is 65°, the range of the reflection spectrum of P-polarized light corresponding to the P-polarized light reflectance R1p of one side in the wavelength band of 460 to 630 nm is range1≦12%.
[0029] Furthermore, range1≦2%.
[0030] The beneficial effect of this technical solution is that it can further improve the smoothness of the reflection spectrum of P-polarized light of the laminated glass, and effectively avoid the influence on the appearance of the laminated glass.
[0031] Furthermore, when the incident angle of the second transparent nanofilm is 65°, the range of the reflection spectrum of P-polarized light corresponding to the P-polarized light reflectance R2p of one side in the wavelength band of 460 to 630 nm is range2≦8%.
[0032] Furthermore, range2 is ≦2%.
[0033] The beneficial effect of this technical solution is that it can further improve the smoothness of the reflection spectrum of P-polarized light of the laminated glass, and effectively avoid the influence on the appearance of the laminated glass.
[0034] Furthermore, the laminated glass has a direct solar reflectance Rds of 30% or more.
[0035] The beneficial effects of the technical solution are that it can effectively increase the direct reflectance of sunlight on the laminated glass, effectively improve the heat insulating effect of the laminated glass, and further improve the heat insulating effect of a head-up display system using the laminated glass, which meets the needs of commercialization and further contributes to improving user convenience.
[0036] Furthermore, the high refractive index material layer includes a first compound, and the first compound includes at least one element selected from the group consisting of Ti, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements.
[0037] Furthermore, the first compound includes at least one of SiN, ZnSnOx, ZnSnMgOx, TiOx, SiZrN, and ZrN.
[0038] Furthermore, the first compound includes at least one of an oxide of Ti, an oxynitride of Ti, a nitride of Ti, and a Ti metal.
[0039] Furthermore, the oxide of Ti contains a first metal element and / or a compound of the first metal element, The first metal element includes at least one of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements.
[0040] Furthermore, the mass ratio of the first metal element in the oxide of Ti is 40% or less.
[0041] Furthermore, the mass ratio of the first metal element in the oxide of Ti is 5% or less.
[0042] Furthermore, the Ti oxynitride contains a second metal element and / or a compound of the second metal element, However, the second metal element includes at least one of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements.
[0043] Furthermore, the mass ratio of the second metal element in the Ti oxynitride is 40% or less.
[0044] Furthermore, the mass ratio of the second metal element in the Ti oxynitride is 5% or less.
[0045] Furthermore, the low refractive index material layer includes a second compound, and the second compound includes at least one of an oxide of Si, an oxynitride of Si, a carbonate of Si, an oxide of Al, and a Si mixture.
[0046] Furthermore, the oxide of Si, the oxynitride of Si, or the carbonate of Si contains a third metal element and / or a compound of the third metal element,
[0047] The third metal element includes at least one of Zr, Nb, Ti, Sb, Sn, Zn, In, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements.
[0048] Furthermore, the mass ratio of the third metal element in the oxide of Si is 30% or less.
[0049] Furthermore, the mass ratio of the third metal element in the oxide of Si is 10% or less.
[0050] Furthermore, the first transparent nanofilm includes a first high refractive index material layer and a first low refractive index material layer;
[0051] The thickness of the first high refractive index material layer is between 45 nm and 120 nm,
[0052] The first low refractive index material layer has a thickness between 90 nm and 200 nm.
[0053] Furthermore, the first transparent nanofilm includes a first high refractive index material layer, a first low refractive index material layer, a second high refractive index material layer, and a second low refractive index material layer, which are arranged in order;
[0054] the first high refractive index material layer has a thickness between 1 nm and 60 nm, the second high refractive index material layer has a thickness between 45 nm and 80 nm,
[0055] The first low refractive index material layer has a thickness between 1 nm and 200 nm, and the second low refractive index material layer has a thickness between 90 nm and 200 nm.
[0056] Further, the first transparent nanofilm includes a first high refractive index material layer, a first low refractive index material layer, a second high refractive index material layer, a second low refractive index material layer, a third high refractive index material layer, and a third low refractive index material layer, which are arranged in order;
[0057] At least one of the first high refractive index material layer, the second high refractive index material layer, and the third high refractive index material layer has a thickness between 45 nm and 80 nm; At least one of the first low refractive index material layer, the second low refractive index material layer, and the third low refractive index material layer has a thickness between 90 nm and 200 nm.
[0058] Furthermore, the first transparent nanofilm includes a metal layer;
[0059] The metal layer includes at least one element of Ti, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, Fe, and rare earth elements.
[0060] Furthermore, the first transparent nanofilm comprises a non-stoichiometric metal compound;
[0061] The non-stoichiometric metal compounds include at least one element of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, Fe, and rare earth elements.
[0062] Furthermore, the high refractive index material layer and / or the low refractive index material layer are provided with sub-layers.
[0063] Furthermore, the first transparent nanofilm is provided with an enhancement layer to improve the performance of the first transparent nanofilm.
[0064] Furthermore, the improving layer includes at least one of a high refractive index material layer, a hydrophobic material layer, and a hydrophilic material layer.
[0065] Furthermore, the thickness of the improved layer is 20 nm or less.
[0066] Furthermore, the thickness of the improved layer is 5 nm or less.
[0067] Furthermore, the conductive layer includes at least one layer having a thickness of 8 nm or less.
[0068] Furthermore, the second transparent nanofilm includes a first dielectric layer, a first conductive layer, and a second dielectric layer, which are arranged in sequence;
[0069] The first dielectric layer has a thickness of 40 nm or more, and the second dielectric layer has a thickness of 50 nm or more;
[0070] The first conductive layer has a thickness between 2 nm and 8 nm.
[0071] Furthermore, the second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, and a third dielectric layer, which are arranged in sequence; The first dielectric layer has a thickness of 25 nm or more, the second dielectric layer has a thickness of 60 nm or more, and the third dielectric layer has a thickness of 40 nm or more; The first conductive layer and / or the second conductive layer has a thickness of 8.0 nm or less.
[0072] Further, the second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, a third dielectric layer, a third conductive layer, and a fourth dielectric layer, which are arranged in sequence;
[0073] the first dielectric layer has a thickness of 25 nm or more, the second dielectric layer has a thickness of 60 nm or more, the third dielectric layer has a thickness of 50 nm or more, and the fourth dielectric layer has a thickness of 30 nm or more; The first conductive layer has a thickness between 5 nm and 12 nm, and the second conductive layer and the third conductive layer each have a thickness between 2 nm and 8 nm.
[0074] Further, the second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, a third dielectric layer, a third conductive layer, a fourth dielectric layer, a fourth conductive layer, and a fifth dielectric layer, which are arranged in sequence;
[0075] The first conductive layer, the second conductive layer, the third conductive layer, and the fourth conductive layer each have a thickness of 8 nm or less.
[0076] Further, the second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, a third dielectric layer, a third conductive layer, a fourth dielectric layer, a fourth conductive layer, a fifth dielectric layer, a fifth conductive layer, and a sixth dielectric layer, which are arranged in order;
[0077] The first conductive layer, the second conductive layer, the third conductive layer, the fourth conductive layer, and the fifth conductive layer each have a thickness of 8 nm or less.
[0078] Furthermore, the conductive layer contains at least one element selected from the group consisting of Ag, Ni, Cr, Cu, Fe, Mn, Pt, Ti, Zn, Sn, Al, Si, and rare earth elements.
[0079] The beneficial effect of this technical solution is that by utilizing Ag-related materials, the direct reflectance of sunlight on the laminated glass can be further increased, thereby more effectively improving the thermal insulation effect of the laminated glass.
[0080] Furthermore, the conductive layer includes Ag or an alloy of Ag.
[0081] Furthermore, the conductive layer and / or the dielectric layer may include sub-layers.
[0082] Furthermore, the dielectric layer has a refractive index of 1.9 or more.
[0083] Furthermore, the dielectric layer contains at least one element of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements.
[0084] Furthermore, the dielectric layer includes oxides of Zn and Sn, and / or nitrides of Si.
[0085] Furthermore, at least one of the dielectric layers contains Zn and Sn, The atomic ratio of Zn to Sn is between 0.4 and 0.6.
[0086] Furthermore, the dielectric layer includes a first functional layer and a second functional layer,
[0087] the first functional layer is used to reduce or prevent the conductive layer from chemically reacting in air and / or during heat treatment; The second functional layer is used to reduce or prevent chemical reactions with the conductive layer during plating of the film.
[0088] Furthermore, the first functional layer contains at least one element of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements.
[0089] Furthermore, the second functional layer comprises a compound of at least one element selected from the group consisting of Zn, Sn, Ga, Al, F, In, V, Li, K, Nb, and Ti, or a mixed compound of at least one element selected from the group consisting of Zn, Sn, Ga, Al, F, In, V, Li, K, Nb, and Ti.
[0090] Furthermore, the laminated glass has a value a in the red-green direction of reflected color of visible light within an incident angle range of 0° to 60°, the value being in the range of −10≦a≦4; The laminated glass has a b value in the yellow-blue direction in the reflected color of visible light within an incident angle range of 0° to 60°, which is in the numerical range of −10≦b≦4.
[0091] The beneficial effect of the technical solution is that it can satisfy the aesthetic requirements of the head-up display system on both the inner glass substrate side and the outer glass substrate side, and can satisfy the aesthetic requirements of the head-up display system at as many angles as possible, not limited to a certain angle.
[0092] Furthermore, the laminated glass has a value a in the red-green direction of reflected color of visible light within an incident angle range of 0° to 70°, the value being in the range of −10≦a≦4; The laminated glass has a b value in the yellow-blue direction in the reflected color of visible light within an incident angle range of 0° to 70°, which is in the numerical range of −10≦b≦4.
[0093] The beneficial effect of this technical solution is that it can better meet the aesthetic requirements of the head-up display system at as many angles as possible, rather than being limited to a certain angle.
[0094] Furthermore, the laminated glass has a value of a in the red-green direction of reflected color of visible light within an incident angle range of 45° to 75°, the value being in the range of −10≦a≦4; The laminated glass has a b value in the yellow-blue direction in the reflected color of visible light within an incident angle range of 45° to 75°, which falls within the numerical range of −10≦b≦4.
[0095] The beneficial effect of this technical solution is that, considering that the mounting angle of vehicles such as trucks and cars is mainly 45°-75°, it utilizes the Brewster angle effect to further contribute to better suppressing ghosting.
[0096] Furthermore, -5≦a≦0 and -5≦b≦0.
[0097] According to a second aspect, the present application provides a head-up display system comprising a projection system and the laminated glass described above.
[0098] Furthermore, the dominant wavelength of said projection system is 460 nm or greater.
[0099] The beneficial effect of the technical solution is that the harm of blue light can be further reduced, so as to further improve the user's experience. Effect of the Invention
[0100] As can be seen from the above technical solution, the present application provides a laminated glass and a head-up display system, the laminated glass including an inner glass substrate, an outer glass substrate, and an intermediate film interposed between the inner glass substrate and the outer glass substrate, a first transparent nano-film for reflecting P-polarized light is provided on one side of the inner glass substrate away from the intermediate film, the first transparent nano-film includes at least one laminated structure consisting of a high refractive index material layer and a low refractive index material layer sequentially deposited from the surface of the inner glass substrate outward, a second transparent nano-film is interposed between the inner glass substrate and the outer glass substrate and is adhered to the intermediate film, the second transparent nano-film is a dielectric The laminated glass includes a dielectric layer and a conductive layer, and each conductive layer is interposed between two of the dielectric layers, the refractive index of the high refractive index material layer is 1.9 or more, and the refractive index of the low refractive index material layer is 1.8 or less, and the laminated glass has a P-polarized light reflectance Rp≧16% when the incident angle is 65°. If the refractive index of the high refractive index material layer is <1.90, or the refractive index of the low refractive index material layer is >1.80, it is difficult to simultaneously obtain high P-polarized light reflectance and spectral smoothness. On the premise of ensuring the requirements of the first transparent nanofilm, for example, using a low refractive index material with a relatively high refractive index, such as the refractive index of the low refractive index material being 1.7, can reduce the thickness of the low refractive index material layer and contribute to reducing production costs. In addition, the P-polarized light reflectance of the laminated glass and the smoothness of the reflection spectrum by P-polarized light can be improved at the same time, and the brightness and display comfort of the head-up display system using the laminated glass can be effectively improved, which meets the needs for commercialization of laminated glass and contributes to improving user convenience.
[0101] In order to more clearly describe the technical solutions in the embodiments of the present application or the prior art, the following will briefly describe the drawings that need to be used in the description of the embodiments or the prior art. Obviously, the drawings in the following description are some examples of the present application, and those skilled in the art can also obtain other drawings based on these drawings without exerting creative efforts. [Brief description of the drawings]
[0102] [Figure 1] FIG. 1 is a partial cross-sectional view of a first representative structure of a head-up display system according to an embodiment of the present application; [Diagram 2] FIG. 1 is a partial cross-sectional view of a second exemplary structure of a head-up display system according to an embodiment of the present application; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0103] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application, and obviously, the described embodiments are only a part of the embodiments of the present application, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present application without any creative efforts belong to the scope of the present application.
[0104] Ordinary HUDs mainly use wedge-shaped PVB, which requires the use of special specification PVB film, the price of which is 7 to 10 times that of ordinary PVB film, and the process difficulty is high, resulting in high material and process costs. It also has poor versatility, requiring different PVBs to be used for different vehicle models.
[0105] In view of this, it is a good option to use a method of plating a film to manufacture a film for HUD and use it in a head-up display system, and its basic principle is to eliminate and suppress ghosting by utilizing the Brewster angle effect of glass. For example, a technical solution of a conductive coating layer containing at least three conductive layers can be utilized, or a technical solution of a conductive coating layer containing at least four conductive layers can be utilized. However, when a technical solution of a conductive coating layer containing two or more conductive layers is utilized, it is difficult to obtain a high P-polarized light reflectance (for example, P-polarized light reflectance ≧ 16%), which greatly affects the brightness of the HUD.
[0106] Alternatively, a film-plated HUD based on the reflection of P-polarized light may be used. One such technical solution involves forming a coating layer capable of reflecting P-polarized light on the surface of an inner glass substrate. However, the high refractive index material used in this technical solution has a low refractive index, e.g., refractive index = 2.33, making it difficult to obtain a high P-polarized light reflectance (e.g., P-polarized light reflectance ≧ 16%).
[0107] As another technical solution, a first coating layer that reflects P-polarized light is formed on the surface of the inner glass substrate, and the inside of the laminated glass is It is being carried out Second Coating Contains an infrared reflective layer (IR layer) At 55°, the P-polarized light reflectance can reach 15% or more, but at that time, the a value of the reflected color of the visible light will already reach 5 or more, resulting in an obvious reddish color, which will greatly affect the use effect of the HUD.
[0108] For HUDs, simply having a high P-polarized light reflectance is not enough. In order to achieve a display of the most neutral color tone possible for the projector image, it is desirable for the reflectance spectrum to be as smooth as possible and to have no significant minima or maxima. Reflection of wavelength band Spect ToIn the above, the difference between the average reflectance at the maximum and the average reflectance at the minimum (based on 100% incident radiation) is at most 5%, more preferably at most 3%, and particularly preferably at most 1%. In practice, a simple superposition of a first coating layer and a second coating layer cannot smooth the reflection spectrum of P-polarized light of the resulting laminated glass, and even if the reflection spectrum of P-polarized light of the first coating layer and the second coating layer is smoothed, it is not possible to smooth the reflection spectrum of P-polarized light of the resulting laminated glass, particularly in the case of a high P-polarized light reflectance.
[0109] At the same time, the HUD is required to have a beautiful appearance on both the inner and outer glass substrates. Generally, the a value of the reflected color that is relatively easy to accept is between -10 and 4, that is, -10≦a≦4, and the b value is also the same. The b value of the reflected color is between -10 and 4, that is, -10≦b≦4, and at the same time, it is necessary to satisfy -10≦a≦4, -10≦b≦4 at as many angles as possible, not limited to a certain angle. In the embodiment of the conventional laminated glass, when the incident angle is 172°, the b value is <-12, and the color is obviously bluish; when the incident angle is 172°, the b value is >5, and the color is obviously yellowish; when the incident angle is 55°, the a value is >5, and the color is obviously reddish; when the incident angle is 172°, the a value is <-13, and the color is obviously greenish; when the incident angle is 55°, the b value is <-12, and the color is obviously bluish; and when the incident angle is 55°, the a value is >5, and the color is obviously reddish. Such poor appearance significantly affects driving comfort.
[0110] In addition, the reflected colors of Rin and Rout in the conventional laminated glass embodiment cannot simultaneously satisfy -10≦a≦4 and -10≦b≦4, and in particular, the reflected color of Rin cannot be satisfied even at two angles of incidence, 55° and 172°. This shows that an aesthetically pleasing film-plated HUD cannot be easily obtained, especially when the P-polarized light reflectance is high (e.g., P-polarized light reflectance ≧15%).
[0111] HUD requires thermal insulation, and Ag, etc. Insulation Material-free HUD but However, its direct solar reflectance Rds (or Re) is about 10%, which is disadvantageous in terms of thermal insulation.
[0112] Based on this, conventional laminated glass has problems such as low reflectance of P-polarized light and poor smoothness of the reflection spectrum of P-polarized light. In contrast, an embodiment of the present application provides laminated glass, which includes an inner glass substrate, an outer glass substrate, and an intermediate film interposed between the inner glass substrate and the outer glass substrate. A first transparent nanofilm for reflecting P-polarized light is provided on one side of the inner glass substrate away from the intermediate film, and the first transparent nanofilm is a high-transparent nanofilm that is sequentially deposited from the surface of the inner glass substrate outward. The laminated glass includes at least one laminated structure consisting of a refractive index material layer and a low refractive index material layer, and a second transparent nanofilm is interposed between the inner glass substrate and the outer glass substrate and is adhered to the intermediate film, and the second transparent nanofilm includes a dielectric layer and a conductive layer, and each conductive layer is interposed between two of the dielectric layers, and the refractive index of the high refractive index material layer is 1.9 or more, and the refractive index of the low refractive index material layer is 1.8 or less, and the laminated glass has a P-polarized light reflectance Rp≧16% when the incident angle is 65°. If the refractive index of the high refractive index material layer is <1.90 or the refractive index of the low refractive index material layer is >1.80, it is difficult to simultaneously obtain high P-polarized light reflectance and spectral smoothness. On the premise of ensuring the requirements of the first transparent nanofilm, a high refractive index material is used as the low refractive index material, for example, the refractive index of the low refractive index material is 1.7, which contributes to reducing the thickness of the low refractive index material layer and reducing production costs. In addition, it is possible to simultaneously improve the P-polarized light reflectance of the laminated glass and the smoothness of the reflection spectrum due to P-polarized light, and it is also possible to effectively improve the brightness and display comfort of a head-up display system using the laminated glass, thereby meeting the needs for commercialization of laminated glass and contributing to improving user convenience.
[0113] The laminated glass can be applied to a head-up display system, particularly a head-up display system used in glass for automobiles, and the laminated glass is specifically a head-up display windshield that can be used in the head-up display system.
[0114] Based on this, the head-up display system provided by the present application uses a film plating method to manufacture the HUD film, which has good HUD effect and appearance. (1) a projection system capable of projecting P-polarized light; (2) Laminated glass capable of reflecting P-polarized light.
[0115] The laminated glass includes at least an inner glass substrate and an outer glass substrate connected via an intermediate layer (ie, intermediate film) of thermoplastic film.
[0116] The P-polarized light reflectance of the laminated glass is Rp≧16%.
[0117] The reflection spectrum corresponding to the P-polarized light reflectance Rp of the laminated glass is ≦4.0% in the wavelength range of 460 to 630 nm.
[0118] A first transparent nanofilm is provided on the inner glass substrate, and the first transparent nanofilm includes at least one high refractive index material layer with a refractive index of ≧1.9 and one low refractive index material layer with a refractive index ≦1.8, and the first transparent nanofilm has a P-polarized light reflectance R1p≧6% on one side, and the range of the reflection spectrum of P-polarized light corresponding to R1p in the wavelength band of 460 to 630 nm is range1.
[0119] Here, a second transparent nanofilm is provided inside the laminated glass, and the second transparent nanofilm includes at least m conductive layers and (m+1) dielectric layers (m is an integer of 1 or more), with the conductive layer being located between the two dielectric layers. The second transparent nanofilm is: One side of the reflectance R2p of P-polarized light is Range 2 is the range in the wavelength band of 460 to 630 nm in the reflection spectrum by P polarization corresponding to the P polarization reflectance R2p.
[0120] Here, the absolute value of (range1+range2) is 6% or less.
[0121] In one or more embodiments of the present application, the refractive index referred to herein refers to the refractive index when the wavelength of transmitted light is 550 nm. A "layer" referred to herein should be understood as a single layer or a stack of multiple layers.
[0122] In one or more embodiments of the present application, the thicknesses described herein are physical thicknesses.
[0123] In one or more embodiments of the present application, Rp refers to the P-polarized reflectance measured from the inner glass substrate side (i.e., the fourth surface) of the laminated glass when the incident angle is 65° (in accordance with ISO 9050).
[0124] In one or more embodiments of the present application, R1p refers to the P-polarized light reflectance of one side of the first transparent nanofilm when the incident angle is 65°. For measuring the P-polarized light reflectance R1p of one side, (1) sample preparation: outside Side glass substrate 2 The surface of the second transparent Nano Coating When the sample is as shown in Figure 2, the third surface of the inner glass substrate is frosted and then blackened. (2) Measurement: The reflection spectrum of P-polarized light is obtained by measuring from the inner glass substrate side, and R1p is calculated in accordance with ISO9050.
[0125] In one or more embodiments of the present application, R2p is the second transparent nanofilm One-sided P-polarized light reflectance, when the incident angle is 65° For convenience of measurement, The above laminated glass Second 2. Transparent nanofilm Although it includes , before The first transparent nanofilm is not included. stomach. Regarding the measurement of R2p, (1) sample preparation: The fourth surface in Figures 1 and 2 is subjected to surface treatment such as polishing, and the laminated glass contains only the second transparent nanofilm. (2) Measurement is performed from the fourth surface of the laminated glass to obtain a reflectance spectrum using P-polarized light, and R2p is calculated in accordance with ISO9050.
[0126] In one or more embodiments of the present application, TL refers to the integrated visible light transmittance (according to ISO 9050) at normal incidence and is measured from the outer glass substrate side with an A illuminant.
[0127] In one or more embodiments of the present application, a represents the red-green value of the color of visible light at a specified angle of incidence based on the CIE 1976, D65 illuminant.
[0128] In one or more embodiments of the present application, b denotes the yellow-blue value of the color of visible light at a specified angle of incidence based on the CIE 1976, D65 illuminant.
[0129] In one or more embodiments of the present application, Rds (or Re) refers to solar direct reflectance according to ISO9050.
[0130] Specifically, each of the following embodiments and application examples will be described in detail.
[0131] (1) In order to solve the problems of conventional laminated glass such as low P-polarized light reflectance and poor smoothness of the reflection spectrum of P-polarized light, the present application provides an embodiment of laminated glass. See Figures 1 and 2. The laminated glass applied to the head-up display system specifically includes the following:
[0132] The optical element includes an inner glass substrate 11, an outer glass substrate 12, and an intermediate film 13 interposed between the inner glass substrate 11 and the outer glass substrate 12. A first transparent nanofilm 14 for reflecting P-polarized light is provided on one side of the inner glass substrate 11 away from the intermediate film 13. The first transparent nanofilm 14 includes at least one laminated structure consisting of a high refractive index material layer and a low refractive index material layer deposited in order from the surface of the inner glass substrate 11 outward. A second transparent nanofilm 15 is interposed between the inner glass substrate 11 and the outer glass substrate 12 and is adhered to the intermediate film 13. The second transparent nanofilm 15 includes a dielectric layer and a conductive layer, and each of the conductive layers is interposed between two of the dielectric layers.
[0133] Here, the high refractive index material layer has a refractive index of 1.9 or more, the low refractive index material layer has a refractive index of 1.8 or less, and the laminated glass has a P-polarized light reflectance Rp≧16% when the incident angle is 65°.
[0134] As shown in FIG. 1 and FIG. 2 , the head-up display system described in the present application includes at least a laminated glass 1 and a projection system 100. The laminated glass 1 includes at least an inner glass substrate 11, an outer glass substrate 12, an intermediate film 13 interposed between the inner glass substrate 11 and the outer glass substrate 12, and a first transparent substrate 13 located on the inner glass substrate 11. Nano Coating and a second transparent substrate interposed between the inner glass substrate 11 and the outer glass substrate 12. Nano CoatingIn the present application, the outer glass substrate-air interface, which is the surface of the outer glass substrate 12 farthest from the intermediate film, is defined as the first surface, the outer glass substrate-intermediate film interface, which is the surface of the outer glass substrate 12 closest to the intermediate film, is defined as the second surface, the inner glass substrate-intermediate film interface, which is the surface of the inner glass substrate 11 closest to the intermediate film, is defined as the third surface, and the inner glass substrate-air interface, which is the surface of the inner glass substrate 11 farthest from the intermediate film, is defined as the fourth surface. In FIG. 1 and FIG. 2, the first transparent nanofilm 14 is deposited on the fourth surface, FIG. 1 shows that the second transparent nanofilm 15 is deposited on the second surface, and FIG. 2 shows that the second transparent nanofilm 15 is deposited on the third surface. The distance from the second transparent nanofilm to the first transparent nanofilm is defined as H.
[0135] In FIG. 1 and FIG. 2, P-polarized light 101 generated by a projection system 100 is incident on the first transparent nanofilm 14 at a certain incident angle, and a first reflected light 102 generated by a part of the P-polarized light 101 being reflected by the transparent nanofilm 14 forms a head-up display image Image1 that can be seen by the human eye 200, and another part of the P-polarized light passes through the transparent nanofilm 14 and propagates through the laminated glass. When the P-polarized light propagating through the laminated glass reaches the second transparent nanofilm 15 on the second surface or the second transparent nanofilm 15 on the third surface, a part of the P-polarized light is reflected, refracted and emitted from the fourth surface to generate a first refracted light 103, and forms a head-up display image Image2. Here, Image1 is generated by the first transparent nanofilm, and Image2 is generated by the second transparent nanofilm. Here, Image1 may be the main image, and Image2 may be the main image or the sub-image. When Image2 is the main image, the second transparent nanofilm 15 One-sided P polarization reflectance R2pSetting R1p / Rp≧0.9 can be achieved by using ultra-thin glass or a wedge-shaped intermediate film, and the distance from the second transparent nanofilm to the first transparent nanofilm is H≦1.8 mm, and the thicknesses of the first transparent nanofilm and the second transparent nanofilm are H≦1.6 mm, H≦1.2 mm, H≦0.8 mm, and H≦0.3 mm. In addition, a wedge-shaped intermediate film with a wedge angle of 0.3 to 0.8 mrad is used. When R1p / Rp≧0.9, the second transparent nanofilm 15 One-sided P polarization reflectance R2p is set to be less than 2%, in which case the brightness ratio between Image1 and Image2 is large enough that the image of Image2 is barely visible and no ultra-thin glass or wedge-shaped intermediate film is required.
[0136] In order to obtain a high brightness HUD image, the P-polarized light reflectance of the laminated glass described in the present application is Rp≧16%, preferably Rp≧20%, which contributes to meeting the needs of commercialization. Therefore, the P-polarized light reflectance R1p of the first transparent nanofilm is ≧6%, otherwise it is disadvantageous to obtain a high P-polarized light reflectance. Furthermore, the higher the reflectance of the first transparent nanofilm, the higher the R1p / Rp ratio, which increases the design freedom of the second transparent nanofilm without relying on a wedge-shaped intermediate film and / or reducing the requirements of the second transparent nanofilm, and therefore R1p≧10%, preferably R1p≧15%.
[0137] The first transparent nanofilm includes at least one high refractive index material layer having a refractive index of ≧1.90 and one low refractive index material layer having a refractive index of ≦1.80. The requirements of the first transparent nanofilm can be realized by combining the high refractive index material layer and the low refractive index material layer. If the refractive index of the high refractive index material layer is <1.90, or if the refractive index of the low refractive index material layer is >1.80, it is difficult to simultaneously obtain high P-polarized light reflectance and spectral smoothness. On the premise of ensuring the requirements of the first transparent nanofilm, for example, if the refractive index of the low refractive index material is 1.7, using a material with a high refractive index as the low refractive index material can contribute to reducing the thickness of the low refractive index material layer and reduce production costs.
[0138] In one embodiment of the present application, the first transparent nanofilm includes at least one high refractive index material layer with a refractive index of ≧2.4 and one low refractive index material layer with a refractive index of ≦1.6. The combination of the high refractive index material layer and the low refractive index material layer can achieve the requirements of the first transparent nanofilm and at the same time contribute to improving the appearance of the HUD.
[0139] In one embodiment of the present application, at least one of the high refractive index material layers has a thickness of 45 nm or more and a refractive index of 2.4 or more, that is, the first transparent nanofilm includes at least one high refractive index material layer with a thickness of ≧45 nm and a refractive index of ≧2.4, thus contributing to achieving high spectral smoothness of P-polarized light and improving the appearance of the HUD.
[0140] (2) After solving the problems of low P-polarized light reflectance and poor smoothness of the reflection spectrum of P-polarized light existing in conventional laminated glass, the present application further solves the influence of conventional laminated glass on the color development effect and further solves the problem of insufficient smoothness of the reflection spectrum of P-polarized light. In order to realize the display of the HUD image with the most neutral color tone possible, the reflection spectrum curve should be as smooth as possible without significant minimum and maximum. The range required by the conventional technology is 450nm to 650nm. Wavelength band of reflection Spect Inside the room However, in the case of HUD, it is sufficient that the reflection spectrum curve is smooth within the wavelength range of 460nm to 630nm, because the wavelength range of 460nm to 630nm includes the wavelengths of three colors, red, green, and blue, which is advantageous for the selection of film systems and layer materials.
[0141] In the present application, the reflection spectrum of P-polarized light corresponding to the Rp described in the present application is smooth, that is, at least in the wavelength range of 460 nm to 630 nm, measured from the inner glass substrate side of the laminated glass. If P polarized light reflectance Corresponding to P polarized reflection The spectrum (based on 100% incident radiation) is within 4% coverage, and preferably within 2% coverage, thus meeting commercial needs.
[0142] For ease of explanation, in this application, the reflection spectrum of P-polarized light corresponding to the above-mentioned R1p is defined as range 1 in the wavelength band of 460 to 630 nm. The reflection spectrum of P-polarized light corresponding to the above-mentioned R2p is defined as range 2 in the wavelength band of 460 to 630 nm. The maximum value of the spectral reflectance corresponding to range 1 Wavelength of Time appears in the blue light wavelength band, i.e., between 460nm and 480nm, range1 takes a positive value, and conversely, the maximum value of the spectral reflectance corresponding to range1 Wavelength of TimeWhen the wavelength of the blue light appears in the non-blue light wavelength band, range1 takes a negative value. The maximum value of the spectral reflectance corresponding to range2 Wavelength of Time appears in the blue light wavelength band, i.e., between 460nm and 480nm, range2 takes a positive value, and conversely, the maximum value of the spectral reflectance corresponding to range2 Wavelength of Time appears in the non-blue light wavelength band, range2 takes a negative value. For example, the maximum value of the reflectance spectrum corresponding to R1p above Wavelength of Time appears in the wavelength band of blue light and has a range of 3%, range1 is 3%, and the maximum value of the reflectance spectrum corresponding to R1p Wavelength of Time appears in the wavelength band of non-blue light and has a range of 3%, then range1 is −3%. In addition to the fact that range1 and range2 above can be negative values, all other ranges described in this application are positive values.
[0143] In order to smooth the reflection spectrum of P polarized light corresponding to the Rp, the applicant has found that when the absolute value of the sum of range1 and range2 is ≦6%, that is, when the absolute value of (range1+range2) is ≦6%, the reflection spectrum of P polarized light of the laminated glass can be easily achieved to be smooth. More preferably, the absolute value of (range1+range2) is ≦3%, and in this case, even if the wavelengths corresponding to the maximum and minimum values of the P polarized light spectral reflectance of the first transparent nanofilm are completely consistent with the wavelengths corresponding to the maximum and minimum values of the P polarized light spectral reflectance of the second transparent nanofilm within the wavelength band of 460 nm to 630 nm, the reflection spectrum of P polarized light of the laminated glass can be smoothed. In addition, when range1 and range2 are both positive or negative, the absolute value of (range1+range2) is ≦6%, and preferably the absolute value of (range1+range2) is ≦3%. Alternatively, when one of range1 and range2 is positive and the other is negative, the absolute value of (range1+range2) is ≦6%, and preferably the absolute value of (range1+range2) is ≦3%.
[0144] In order to smooth the reflection spectrum of P polarized light corresponding to Rp, the reflection spectrum of P polarized light corresponding to R1p has a range of ≦12.0%, preferably ≦5%, in the wavelength band of 460 to 630 nm, i.e., the absolute value of range1 is ≦12.0%, preferably ≦5%, more preferably ≦2%. If the reflection spectrum of P polarized light corresponding to R1p has a range of >12.0% in the wavelength band of 460 to 630 nm, it is difficult to smooth the reflection spectrum of P polarized light corresponding to Rp and / or the appearance of the laminated glass is affected.
[0145] In order to smooth the reflection spectrum of the P polarized light corresponding to Rp, the reflection spectrum of the P polarized light corresponding to R2p has a range of ≦8.0%, preferably ≦5%, more preferably ≦2% in the wavelength band of 460 to 630 nm, that is, the absolute value of range2 is ≦8.0%, preferably ≦5%, more preferably ≦2%. If the reflection spectrum of the P polarized light corresponding to R2p has a range of >8.0% in the wavelength band of 460 to 630 nm, it is difficult to smooth the reflection spectrum of the P polarized light corresponding to Rp.
[0146] (3) In order to solve the problems of the conventional laminated glass such as low P-polarized light reflectance and poor smoothness of the reflection spectrum due to P-polarized light, and further solve the problems of the conventional laminated glass such as poor thermal insulation effect, the present application provides an embodiment of laminated glass, in which the second transparent nanofilm described in the present application contains a conductive layer, and therefore has a thermal insulation function, and its direct solar reflectance Rds is ≧20%, preferably Rds ≧25%, and more preferably Rds ≧30%, which can effectively increase the direct solar reflectance of the laminated glass, effectively improve the thermal insulation effect of the laminated glass, and also effectively improve the thermal insulation effect of the head-up display system using the laminated glass, thereby meeting the needs of commercialization and further contributing to improving user convenience.
[0147] In addition, the second transparent nano-film includes a conductive layer and is suitable for use in electrical heating, allowing for rapid dehumidification, defog, and even deicing. Therefore, the laminated glass of the present invention may have an electrical heating function and is very suitable for a power supply of 8V to 48V. Second transparent Nano Coating When a bus bar is provided, it can be connected to the electrode of the power supply, and the above-mentioned Second transparent nanocoating It becomes possible to introduce a current into the
[0148] In one embodiment of the present application, the high refractive index material layer includes a first compound of at least one element selected from the group consisting of Ti, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, rare earth elements, etc. Acid-base resistant compounds are preferred, including but not limited to SiN, ZnSnOx, ZnSnMgOx, TiOx, SiZrN, ZrN, etc.
[0149] In one embodiment of the present application, the high refractive index material layer is selected from at least one of Ti oxide, Ti oxynitride, Ti nitride, and Ti metal. Optionally, the Ti oxide includes one or more of a first metal element and its compounds, and the first metal element includes, but is not limited to, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, rare earth elements, etc. For example, the Ti oxide includes one or more of ZrO2, WO3, MoO2, and Y2O3. Of course, the Ti oxide may include one or more of ZrN and SiN, if necessary. Preferably, the proportion of the Ti oxide that is occupied by the first metal element is 40 mass% or less. For example, when the Ti oxide contains Si oxide, the mass of the Si oxide / (mass of the Si oxide+mass of the Ti oxide)≦40%. For example, when the Ti oxide contains Sn oxide and Zr oxide, the mass of the Sn oxide+mass of the Zr oxide) / (mass of the Sn oxide+mass of the Zr oxide+mass of the Ti oxide)≦40%. If the mass% of the first metal element exceeds 40%, it is difficult to obtain a high refractive index material with a refractive index of ≧2.4, so the mass% of the first metal element does not exceed 20%, more preferably, the mass% of the first metal element exceeds 10%, and most preferably, the mass% of the first metal element does not exceed 5%. Optionally, the Ti oxynitride may contain one or more of other second metal elements and their compounds, including, but not limited to, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, rare earth elements, etc. For example, the Ti oxynitride may contain one or more of ZrO2, Bi2O3, HfO2, MoO2, and Y2O3. Of course, if necessary, the Ti oxynitride may contain one or more of ZrN and SiN. In one embodiment of the present application, the proportion of the Ti oxynitride that is occupied by the second metal element is 40 mass% or less.For example, when the Ti oxynitride contains Zr oxide, the mass of Zr oxide / (mass of Zr oxide+mass of Ti oxynitride) is ≦40%. For example, when the Ti oxynitride contains Zn oxide and Zr nitride, the mass of Zn oxide+mass of Zr nitride / (mass of Zn oxide+mass of Zr nitride+mass of Ti oxynitride) is ≦40%. If the mass% of the second metal element exceeds 40%, it is difficult to obtain a high refractive index material with a refractive index of ≧2.4, so the mass% of the second metal element does not exceed 20%, more preferably, the mass% of the second metal element exceeds 10%, and most preferably, the mass% of the metal element does not exceed 5%.
[0150] In one embodiment of the present application, the low refractive index material layer is selected from at least one of oxides of Si, oxynitrides of Si, carbonates of Si, oxides of Al, and mixtures thereof. For example, a mixture of SiO2 and SiOxNy, SiAlOx, porous Al2O3, porous SiO2, etc. Optionally, the oxides of Si, oxynitrides of Si, and carbonates of Si may contain one or more other third metal elements and compounds thereof, and the third metal elements include, but are not limited to, Zr, Nb, Ti, Sb, Sn, Zn, In, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, rare earth elements, etc. For example, the oxides of Si include one or more of ZrO2, SiN, MoO2, and Y2O3. In one embodiment of the present application, the proportion of the oxides of Si that are occupied by the third metal elements is 30 mass% or less. For example, when the oxide of Si contains MgO, the mass of MgO / (mass of the oxide of Si+mass of MgO) is ≦40%. If the mass% of the third metal element exceeds 30%, it is difficult to obtain a low refractive index material with a refractive index ≦1.6, so the mass% of the third metal element does not exceed 30%, and more preferably, the mass% of the third metal element exceeds 10%.
[0151] Here, the first transparent nanofilm 14 may have a two-layer, four-layer, and six-layer structure.
[0152] In one embodiment of the present application, the high refractive index layer and the low refractive index material layer may be deposited on the fourth surface of the inner glass substrate 11 in sequence.
[0153] Optionally, the first transparent nanofilm 14 includes one high refractive index material layer and one low refractive index material layer, forming a structure of inner glass substrate 11 / high refractive index material layer (abbreviated as H11) / low refractive index material layer (abbreviated as L11), for example, inner glass substrate 11 / TiOx / SiO2, for example, inner glass substrate 11 / TiOx / porous Al2O 3 Preferably, the thickness of the high refractive index material layer H11 is between 45 nm and 120 nm, otherwise it will affect the spectral smoothness of the HUD and / or the HUD appearance. Preferably, the thickness of the low refractive index material layer L11 is between 90 nm and 200 nm, otherwise it will affect the spectral smoothness of the HUD and / or the HUD appearance.
[0154] Optionally, the first transparent nanofilm 14 includes two high refractive index material layers and two low refractive index material layers, forming a structure of inner glass substrate 11 / high refractive index material layer (abbreviated as H22) / low refractive index material layer (abbreviated as L22) / high refractive index material layer (abbreviated as H21) / low refractive index material layer (abbreviated as L21). For example, inner glass substrate 11 / TiOx / SiO2 / TiOx / SiO2, for example, inner glass substrate 11 / TiOx / SiO2 / TiOxNy / SiAlOx. Preferably, the thickness of the high refractive index material layer H21 is between 45 and 80 nm. Preferably, the thickness of the high refractive index material layer H22 is between 1 and 60 nm.
[0155] Preferably, the thickness of the low refractive index material layer L21 is between 90 and 200 nm. Preferably, the thickness of the low refractive index material layer L22 is between 1 nm and 200 nm. Otherwise, it may affect the spectral smoothness of the HUD and / or the appearance of the HUD.
[0156] Optionally, the first transparent nanofilm 14 includes three high refractive index material layers and three low refractive index material layers, forming a structure of inner glass substrate 11 / high refractive index material layer (abbreviated as H33) / low refractive index material layer (abbreviated as L33) / high refractive index material layer (abbreviated as H32) / low refractive index material layer (abbreviated as L32) / high refractive index material layer (abbreviated as H31) / low refractive index material layer (abbreviated as L31).
[0157] For example, inner glass substrate 11 / TiOx / SiO2 / TiOx / SiO2 / TiOx / TiOxNy / SiAlOx / ; for example, inner glass substrate 11 / TiOxNy / SiO2 / TiOxNy / SiO2 / TiOx / TiOxNy / SiAlOx / .
[0158] Preferably, at least one of the high refractive index material layers H31, H32, and H33 has a thickness between 45 and 80 nm, and preferably, at least one of the low refractive index material layers L31, L32, and L33 has a thickness between 90 and 200 nm.
[0159] In one embodiment of the present application, the first transparent nanofilm includes a metal layer, and the metal layer is selected from at least one element such as Ti, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, Fe, rare earth elements, etc. Metal elements or alloys that are resistant to oxidation and acid-alkali corrosion are preferred, including but not limited to Ni, Cr, stainless steel, NiCr, Ti, etc.
[0160] In one embodiment of the present application, the first transparent nanofilm comprises a non-stoichiometric metal compound, the metal compound being selected from at least one element such as Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, Fe, rare earth elements, etc. A non-stoichiometric compound of a metal element or alloy that is resistant to oxidation, acid-alkali corrosion, is preferred, including but not limited to NiOx (where x<1), CrOx (where x<1), NiCrNx (where x<1), SiOx (where x<1.2), etc.
[0161] Here, the first transparent nanofilm 14 may be provided with a sub-layer.
[0162] In one embodiment of the present application, the high refractive index material layer may include sub-layers, such as TiOx / TiOxNy, or may be TiOx / TiZrOx, or may have multiple layers of TiOx with different refractive indices, such as SiN / TiOx / ZnSnOx, depending on the x in TiOx.
[0163] In one embodiment of the present application, the low refractive index material layer may include sub-layers, such as SiO2 / porous SiO2, for example SiO2 / SiAlOx.
[0164] Here, the first transparent nanofilm 14 may be provided with an improvement layer.
[0165] In one embodiment of the present application, the first transparent nanofilm 14 includes an improvement layer, which is located on the outermost side of the first transparent nanofilm 14 and can achieve one or more of the following functions: (1) improving the acid resistance of the first transparent nanofilm 14; (2) improving the alkali resistance of the first transparent nanofilm 14; (3) Improve the color of the HUD; (4) improving the abrasion resistance of the first transparent nanofilm 14; (5) Changing the contact angle of the first transparent nanofilm 14.
[0166] Optionally, the improvement layer is selected from the high refractive index materials, such as TiOx, TiOxNy, SiN, ZnSnOx. In one embodiment of the present application, the thickness of the improvement layer is less than 20 nm, preferably less than 10 nm, more preferably less than 5 nm.
[0167] Alternatively, said improving layer is selected from layers comprising hydrophobic materials, preferably said hydrophobic layer has a contact angle ≧100°.
[0168] Alternatively, said improving layer is selected from layers comprising hydrophilic materials, preferably said hydrophilic layer has a contact angle of ≦20°.
[0169] Here, the second transparent nanofilm 15 may be provided with a low-e (low emissivity) layer.
[0170] The second transparent nanofilm includes at least m conductive layers and (m+1) dielectric layers (m is an integer ≧1), with the conductive layers being located between the two dielectric layers.
[0171] In one embodiment of the present application, the second transparent nanofilm 15 includes at least one conductive layer having a thickness ≦8.0 nm, the conductive layer being disposed between two dielectric layers or layer sequences, respectively. If the thickness of all conductive layers exceeds 8.0 nm, problems may occur in the appearance and / or P-polarized light reflectance and / or P-polarized light spectral smoothness of the HUD.
[0172] Here, the second transparent nanofilm 15 may be provided with a single layer silver layer structure.
[0173] Optionally, the second transparent nanofilm 15 includes one conductive layer and two dielectric layers, forming a structure of first dielectric layer / first conductive layer / second dielectric layer, specifically, as shown in FIG. 1, the outer glass substrate 12 / first dielectric layer / first conductive layer / second dielectric layer, specifically, as shown in FIG. 2, the inner glass substrate 11 / first dielectric layer / first conductive layer / second dielectric layer. Preferably, the thickness of the first dielectric layer is 40 nm or more, the thickness of the second dielectric layer is ≧50 nm, and the thickness of the first conductive layer is 2 nm or more and 8.0 nm or less. Otherwise, problems may occur in the appearance and / or P-polarized light reflectance and / or P-polarized light spectrum smoothness of the HUD.
[0174] Here, the second transparent nanofilm 15 may be provided with a two-layer silver layer structure.
[0175] Optionally, the second transparent nanofilm 15 includes two conductive layers and three dielectric layers, forming a structure of first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer. Specifically, as shown in FIG. 1, the structure is outer glass substrate 12 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer, and specifically, as shown in FIG. 2, the structure is inner glass substrate 11 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer. Optionally, the thickness of the first conductive layer and / or the second conductive layer is 8.0 nm or less. Otherwise, problems may occur in the appearance and / or P-polarized light reflectance and / or P-polarized light spectrum smoothness of the HUD. Preferably, the thickness of the first dielectric layer is ≧25 nm, the thickness of the second dielectric layer is ≧60 nm, and the thickness of the third dielectric layer is ≧40 nm. At least one of the first conductive layer and the second conductive layer has a thickness of 8.0 nm or less, and preferably, the thickness of the first conductive layer is 4 nm or more and 8.0 nm or less, and the thickness of the second conductive layer is 4 nm or more and 8.0 nm or less, in which case, the dependence of the HUD on the thickness of the glass is reduced by contributing to making the display brightness of Image2 darker.
[0176] Here, the second transparent nanofilm 15 may be provided with a three-layer silver layer structure.
[0177] Optionally, the second transparent nanofilm 15 includes three conductive layers and four dielectric layers, forming a structure of first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer, specifically, as shown in FIG. 1, the structure is outer glass substrate 12 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer, and specifically, as shown in FIG. 2, the structure is inner glass substrate 11 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer. Preferably, the thickness of the first dielectric layer is ≧25 nm, the thickness of the second dielectric layer is ≧60 nm, the thickness of the third dielectric layer is ≧50 nm, the thickness of the fourth dielectric layer is ≧30 nm, the thickness of the first conductive layer is ≧5 nm and ≦12 nm, the thickness of the second conductive layer is ≧2 nm and ≦8.0 nm, and the thickness of the third conductive layer is ≧2 nm and ≦8.0 nm.
[0178] Here, the second transparent nanofilm 15 may be provided with a four-layer silver layer structure.
[0179] Optionally, the second transparent nanofilm 15 includes four conductive layers and five dielectric layers, forming a structure of first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer / fourth conductive layer / fifth dielectric layer. Specifically, as shown in FIG. 1, the structure is outer glass substrate 12 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer / fourth conductive layer / fifth dielectric layer. Specifically, as shown in FIG. 2, the structure is inner glass substrate 11 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer / fourth conductive layer / fifth dielectric layer. Preferably, the first conductive layer, the second conductive layer, the third conductive layer and the fourth conductive layer each have a thickness of 8.0 nm or less.
[0180] Here, the second transparent nanofilm 15 may be provided with a five-layer silver layer structure.
[0181] Optionally, the second transparent nanofilm 15 includes five conductive layers and six dielectric layers, forming a structure of first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer / fourth conductive layer / fifth dielectric layer / fifth conductive layer / sixth dielectric layer. Specifically, as shown in FIG. 1, the structure is outer glass substrate 12 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer / fourth conductive layer / fifth dielectric layer / fifth conductive layer / sixth dielectric layer. Specifically, as shown in Fig. 2, the order is: inner glass substrate 11 / first dielectric layer / first conductive layer / second dielectric layer / second conductive layer / third dielectric layer / third conductive layer / fourth dielectric layer / fourth conductive layer / fifth dielectric layer / fifth conductive layer / sixth dielectric layer. Preferably, the thicknesses of the first conductive layer, second conductive layer, third conductive layer, fourth conductive layer, and fifth conductive layer are all 8.0 nm or less.
[0182] In one embodiment of the present application, the conductive layer described herein comprises at least one metal element selected from the group consisting of Ag, Ni, Cr, Cu, Fe, Mn, Pt, Ti, Zn, Sn, Al, Si, and rare earth elements, with Ag or an Ag alloy being preferred.
[0183] In one embodiment of the present application, the conductive layer described herein may include sub-layers, for example, the conductive layer may be Ag / Cu / Ag, AgNi / Cr, Ag / AgCu / , NiCr / Ag / NiCr, etc.
[0184] In one embodiment of the present application, the refractive index of the dielectric layer is ≧1.9, and if the refractive index is less than 1.9, it is relatively difficult to obtain an ideal optical appearance.
[0185] In one embodiment of the present application, the dielectric layer comprises at least one element selected from the group consisting of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, rare earth elements, etc. Preferably, the dielectric layer comprises at least oxides of Zn and Sn, and / or at least nitride of Si.
[0186] Alternatively, the dielectric layer is a single layer, and preferably contains at least two elements, Zn and Sn, where the atomic ratio of Zn to Sn is between 0.4 and 0.6. For example, a ZnSnOx film can be produced by sputtering using a ceramic target of ZnSnOx. For example, a ZnSnMgOx film can be produced by sputtering using a ceramic target of ZnSnMgOx.
[0187] Optionally, the dielectric layer may include sub-layers, such as ZnSnOx / SiN / ZnSnOx, ZnO / ZnSnNiOx, AZO / SiN / AZO, etc.
[0188] Optionally, the dielectric layer includes at least two functional layers, a first functional layer and a second functional layer.
[0189] Optionally, the first functional layer protects the conductive layer to reduce or avoid chemical reactions of the conductive layer in air and / or during heat treatment. The first functional layer comprises at least one element selected from the group consisting of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, rare earth elements, etc. Preferably, the first functional layer comprises at least oxides of Zn and Sn and / or at least nitrides of Si.
[0190] Optionally, the second functional layer can reduce or avoid chemical reactions of the conductive layer during plating of the film, the material being selected from compounds or mixed compounds of Zn, Sn, Ga, Al, F, In, V, Li, K, Nb, Ti, preferably Zn-based oxides or Zn-based oxide-doped.
[0191] (4) In order to solve the problems of conventional laminated glass, such as low P-polarized light reflectance and poor smoothness of the reflection spectrum due to P-polarized light, and further solve the problem of conventional laminated glass, such as the inability to ensure comfortable appearance at multiple angles, the present application provides an embodiment of laminated glass, in which the numerical range of a value in the red-green direction of the reflected color of visible light of the laminated glass is -10≦a≦4, and the numerical range of b value in the yellow-blue direction of the reflected color of visible light of the laminated glass is -10≦b≦4.
[0192] Specifically, the HUD has aesthetic requirements on both the inner and outer glass substrates. Generally, the a value of the reflected color that is relatively easy to accept is between -10 and 4, i.e., -10≦a≦4, and the b value is also acceptable, and the b value of the reflected color is between -10 and 4, i.e., -10≦b≦4. At the same time, it is necessary to satisfy -10≦a≦4, -10≦b≦4 at as many angles as possible, not limited to a certain angle.
[0193] In one embodiment of the present application, the laminated glass 1 described in the present application has a reflected color value a and a value b that satisfy -10≦a≦4 and -10≦b≦4, preferably -10≦a≦0 and -10≦b≦0, and more preferably -5≦a≦0, -5≦b≦0, at least within an incident angle range of 0 to 60°.
[0194] In one embodiment of the present application, the laminated glass 1 described in the present application has a and b values of its reflected color that satisfy -10≦a≦4 and -10≦b≦4, preferably -10≦a≦0, -10≦b≦0, more preferably -5≦a≦0, -5≦b≦0, at least within the range of an incident angle of 0 to 70°. This can be achieved by the first transparent nanofilm and the second transparent nanofilm.
[0195] Considering that the mounting angle of vehicles such as trucks and cars is mainly 45-75°, the incident angle θB described in the present application may be any angle or angle range between 45-75°, including but not limited to 45-70°, 50-68°, 60-72°, etc. The incident angle is preferably 50°-70°, which is more conducive to utilizing the Brewster angle effect and can better suppress ghosting.
[0196] (5) Based on the above embodiment of the laminated glass, the present application further provides a head-up display system including the laminated glass, which can solve the problems of the conventional laminated glass having low P-polarized reflectance, poor smoothness of the reflection spectrum of P-polarized light, which affects the coloring effect of the conventional laminated glass, and the problems of the conventional laminated glass having poor insulation effect due to the reflection spectrum of P-polarized light with insufficient smoothness, and the conventional laminated glass being unable to ensure a comfortable appearance at multiple angles. The present application utilizes a projection imaging technology using P-polarized light, and the projection system 100 can project P-polarized light 11, but can also project non-P-polarized light, provided that the higher the proportion of the radiation component of P-polarized light, the more advantageous it is for suppressing ghosting, and the proportion of the radiation component of P-polarized light in the P-polarized light 11 is preferably ≧70%, more preferably ≧90%, and most preferably 100%.
[0197] At the same time, the projection system of the head-up display system has a dominant wavelength of 460 nm or more, which contributes to reducing the harmful effects of blue light.
[0198] The projection system 100 described herein includes elements known to those skilled in the art, including, but not limited to, lasers, light emitting diodes (LEDs), liquid crystal displays (LCDs), digital light processing (DLPs), electroluminescence (EL), cathode ray tubes (CRTs), vacuum fluorescent tubes (VFDs), collimators, spherical correction lenses, convex lenses, concave lenses, mirrors, and / or polarizers, etc. At the same time, the position and incidence angle of said projection system 100 are adjustable to meet different position and height requirements.
[0199] The laminated glass shown in Figures 1 and 2 includes an inner glass substrate 11, an outer glass substrate 12, and a thermoplastic film 13, but the laminated glass described herein may further include other substrates, including, but not limited to, materials such as PET and PMMA. The laminated glass described herein may have a structure such as, but not limited to, glass / thermoplastic film / glass / thermoplastic film, glass / thermoplastic film / PET / thermoplastic film / glass, PET / thermoplastic film / glass / thermoplastic film / glass, etc. Thus, the laminated glass described herein includes at least an inner glass substrate 11, an outer glass substrate 12, and a thermoplastic film 13.
[0200] In order to meet the safety requirements for the use of glass for automobiles, the outer glass substrate 12 described in the present application is a physically strengthened curved glass substrate having a thickness of 1.8 mm or more, for example, obtained through high-temperature heat treatment at least at 560° C. and bending. The inner glass substrate 11 may be a physically strengthened curved glass substrate, but from the viewpoint of reducing the weight of automobiles, the inner glass substrate 11 is preferably a non-physically strengthened curved glass substrate having a thickness of 1.6 mm or less. In order to fully utilize the advantageous effect of the inner glass substrate 11 described in the present application in the head-up system described in the present application, for example, to improve the projection brightness at a certain incident angle, a thinner inner glass substrate 11 can obtain a better head-up display effect, and preferably, the thickness of the inner glass substrate 12 is 0.7 to 1.2 mm, and the non-physically strengthened curved glass substrate may be chemically strengthened soda lime silica glass, chemically strengthened aluminosilicate glass, chemically strengthened borosilicate glass, main body reinforced aluminosilicate glass, main body reinforced aluminosilicate glass, main body reinforced borosilicate glass, etc. The chemical strengthening described in this application mainly involves ion exchange on the glass surface by ions of different ionic radii, which generates high surface stress on the glass surface and is accompanied by a certain depth of the stress layer, thereby improving the strength of the mechanical performance of the glass. The main body tempered glass described in this application refers to a glass that does not require physical or chemical strengthening, is directly laminated with other glass to form a laminated glass, and the quality of the laminated glass meets the specifications of laminated glass for automobiles, such as China's GB9656-2016 Automotive Safety Glass.
[0201] The inner glass substrate 11 and the outer glass substrate 12 described in the present application are connected by a thermoplastic film 13. The thermoplastic film described in the present application may be at least one of polycarbonate (PC), polyvinyl chloride (PVC), polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), polyacrylate (PA), polymethyl methacrylate (PMMA), ionic interlayer (SGP), or polyurethane (PU). Of course, the thermoplastic film 13 may be a single-layer structure or a multi-layer structure, and the multi-layer structure may be a two-layer structure, a three-layer structure, a four-layer structure, a five-layer structure, or the like. The thermoplastic film 13 may have other functions, such as reducing the interference of sunlight to human eyes by providing at least one colored region as a shade band, or having a sunscreen or heat insulation function by adding an infrared absorbing agent, or having an ultraviolet absorbing agent to block ultraviolet rays, or having a sound insulation function by increasing the plasticizer content of one layer of the thermoplastic film 13 of the multi-layer structure. In order to eliminate perspective ghosts that occur when the scenery in the vehicle's external environment passes through the windshield, preferably, the thermoplastic film 13 has a wedge-shaped cross-sectional profile, and the wedge angle of the wedge-shaped cross-sectional profile is 0.01 to 0.18 mrad, for example, 0.05 mrad, 0.10 mrad, 0.15 mrad, 0.18 mrad, etc. In this way, even if a thermoplastic film 13 with a small wedge angle is used, it is possible to simultaneously eliminate reflection ghosts and perspective ghosts at low cost, thereby obtaining a higher quality head-up display image and observation effect.
[0202] The visible light transmittance described in this application is TL≧50%, and in order to meet the safety requirements in the use of glass for automobiles, preferably the visible light transmittance described in this application is TL≧70%.
[0203] In one embodiment of the present application, the second transparent nano-film described in the present application includes a conductive layer, so it is suitable for use in electrical heating, and can quickly dehumidify, remove fog, and even de-icing. The laminated glass of the present application may further have an electrical heating function, and is very suitable for a power supply of 8V to 48V. Second transparent nanocoating When the bus bar is provided, it is connected to the electrode of the power supply and the above-mentioned is performed in as wide a part as possible of the width of the glass substrate. Second transparent nanocoating The busbar may be one or more of silver paste, copper foil, and aluminum foil. When the power supply voltage is 48V and the width between the busbars on the glass substrate is 0.7m, the power of the electric heating is 3000W / m 2 It can be more than that.
[0204] In order to further explain the solution of the present application with respect to the above content, the present application further provides the following examples and comparative examples for illustrative purposes, which are all formed by a production process such as hot bending of automotive glass after film plating is completed.
[0205] In the following Ag alloy, the mass percentage of Ag is 98%, and the rest is the mass percentage of the doping element. For example, in the case of AgNi, the mass percentage of Ag is 98%, and the mass percentage of Ni is 2%.
[0206] (1) Comparative Example 1 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0207] First transparent nanofilm film system: inner glass substrate 11 / TZO (45.5 nm) / SiO2 (120 nm), where TZO is ZnO doped TiOx with refractive index = 2.33; The film system of the second transparent nanofilm is: outer glass substrate 12 / ZnSnOx(19 nm) / ZnO(10 nm) / Ag(10.5 nm) / TiOx(6 nm) / ZnSnOx(66 nm) / ZnO(10 nm) / Ag(9.4 nm) / TiOx(5.3 nm) / ZnSnOx(19 nm) / TiOx(6 nm).
[0208] The thickness of the PVB is 0.76 mm.
[0209] The inner glass substrate 11 is made of soda-lime silica glass and has a thickness of 1.6 mm.
[0210] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0211] (2) Comparative Example 2 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / second transparent nanofilm / PVB / outer glass substrate 12.
[0212] The film system of the first transparent nanofilm: inner glass substrate 11 / ZnSnOx (25.0 nm) / TiOx (44.0 nm) / SiO2 (110 nm).
[0213] The film system of the second transparent nanofilm is: inner glass substrate 11 / ZnSnOx(22.0nm) / ZnO(10nm) / Ag(7.5nm) / NiCr(0.1nm) / AZO(10nm) / ZnSnOx(40nm) / ZnO(10nm) / Ag(8.0nm) / NiCr(0.1nm) / AZO(10nm) / ZnSnOx(84.5nm) / ZnO(10nm) / Ag(7.5nm) / NiCr(0.1nm) / AZO(10nm) / ZnSnOx(34nm) / SiN(6nm). AZO is aluminum doped zinc oxide.
[0214] The thickness of the PVB is 0.76 mm.
[0215] The inner glass substrate 11 is made of soda-lime silica glass and has a thickness of 1.6 mm.
[0216] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0217] (3) Example 1 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0218] First transparent nanofilm film system: fourth surface of laminated glass / TiSnOx (60 nm) / SiO2 (100 nm), where TiSnOx has a refractive index of 2.40.
[0219] The second transparent nanofilm was prepared in the following film system: second surface of laminated glass / ZnSnOx (43 nm) / ZnO (10 nm) / AgTi (7.4 nm) / AZO (10 nm) / ZnSnOx (96.7 nm) / SiN (5 nm), where the mass ratio of Ti in AgTi is 1%.
[0220] The thickness of the PVB is 0.76 mm.
[0221] The inner glass substrate 11 is made of soda-lime silica glass and has a thickness of 1.6 mm.
[0222] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0223] (4) Example 2 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0224] First transparent nanofilm film system: fourth surface of laminated glass / TiOx(5 nm) / TiBiOx(100 nm) / SiO2(110 nm), where the refractive index of TiBiOx is 2.41.
[0225] The second transparent nanofilm had a film system: second surface of laminated glass / ZnSnOx(43.5 nm) / Ag(11.9 nm) / ZnSnOx(111.2 nm) / Ag(6.0 nm) / ZnSnOx(40 nm) / SiZrN(5 nm).
[0226] The thickness of the PVB is 0.76 mm.
[0227] The inner glass substrate 11 is made of soda-lime silica glass and has a thickness of 1.6 mm.
[0228] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0229] (5) Example 3 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0230] First transparent nanofilm film system: fourth surface of laminated glass / ZnSnMgOx(19.5 nm) / SiO2(10.0 nm) / TiOx(10.0 nm) / TiAlOx(38.0 nm) / SiO2(111 nm), where the refractive index of TiOx is 2.60 and the refractive index of TiAlOx is 2.50.
[0231] Second transparent nanofilm film system: 3rd surface of laminated glass / ZnSnNiOx(32.0nm) / Ag(5.0nm) / AZO(10nm) / SiN(58.0nm) / GZO(10nm) / Ag(5.0nm) / NiCr(0.3nm) / AZO(10nm) / ZnSnOx(74.8nm) / SiN(5nm). GZO is gallium doped zinc oxide.
[0232] The thickness of the PVB is 0.76 mm.
[0233] The inner glass substrate 11 is made of aluminoborosilicate glass and has a thickness of 0.7 mm.
[0234] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0235] (5) Example 4 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0236] First transparent nanofilm film system: fourth surface of laminated glass / TiOx(5.0 nm) / SiN(10.0 nm) / SiO2(10.0 nm) / TiOx(50.0 nm) / SiO2(108.0 nm), where the refractive index of TiOx is 2.58.
[0237] The film system of the second transparent nanofilm is: third surface of laminated glass / ZnSnOx(5.0nm) / SiN(33.0nm) / AZO(10.0nm) / AgCu(11.3nm) / ZnO(10.0nm) / ZnSnSiOx(20.0nm) / ZnSnOx(33.0nm) / ZnO(10.0nm) / Ag(6.6nm) / AZO(10.0nm) / ZnSnOx(64.5nm) / AZO(10nm) / AgTi(5.1nm) / ZnO(10.0nm) / ZnSnOx(20.0nm) / SiN(35nm).
[0238] The thickness of the PVB is 0.76 mm.
[0239] The inner glass substrate 11 is made of SiO2 glass and has a thickness of 1.1 mm.
[0240] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0241] (7) Example 5 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0242] The film system of the first transparent nanofilm is: fourth surface of laminated glass / TiSnOx(10.8 nm) / SiO2(62.3 nm) / TiMgOx(14.0 nm) / SiO2(31.8 nm) / TiOx(76.7 nm) / SiO2(110.0 nm), where the refractive indexes of TiSnOx and TiMgOx are 2.50, and the refractive index of TiOx is 2.60.
[0243] Film system of the second transparent nanofilm: second surface of laminated glass / ZnSnMnOx(10.0nm) / SiN(45.0nm) / AZO(10.0nm) / AgCr(5.0nm) / ZnO(10.0nm) / ZnSnZr(5.0nm) / ZnSnOx(60.0nm) / ZnO(10.0nm) / Ag(4.3nm) / AZO(10.0nm) / ZnSnOx(39.0nm) / AZO(10nm) / AgTi(5.0nm) / ZnO(10.0nm) / ZnSnOx(61.0nm) / AZO(10.0nm) / Ag(5.0nm) / ZnO(10.0nm) / ZnSnOx(20.0nm) / ZnSnMgAlOx(10.0nm) / SiN(5nm).
[0244] The thickness of the PVB is 0.76 mm.
[0245] The inner glass substrate 11 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0246] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0247] (8) Example 6 Laminated glass structure: first transparent nanofilm / inner glass substrate 11 / PVB / second transparent nanofilm / outer glass substrate 12.
[0248] First transparent nanofilm film system: fourth surface of laminated glass / SiN(40.0 nm) / TiOx(50.0 nm) / SiO2(110.0 nm), where the refractive index of TiOx is 2.62.
[0249] Second transparent nanofilm film system: Second surface of laminated glass / SiN(20.0nm) / ZnSnM gAl Ox(10.0nm) / AZO(10.0nm) / AgNb(3.6nm) / ZnO(10.0nm) / ZnSnOx(60.5nm) / ZnO(10.0nm) / Ag(4.3nm) / AZO(10.0nm) / ZnSnOx(39.5nm) / AZO(10nm) / AgNiTi(5.0nm) / ZnO(10.0nm) / ZnSnOx(61.0nm) / AZO(10.0nm) / Ag(5.6nm) / ZnO(10.0nm) / ZnSnOx(20.0nm) / ZnSnMgAlOx(8.0nm) / SiN(5nm).
[0250] The thickness of the PVB is 0.76 mm.
[0251] The inner glass substrate 11 is borosilicate glass and has a thickness of 2.1 mm.
[0252] The outer glass substrate 12 is made of soda-lime silica glass and has a thickness of 2.1 mm.
[0253] Table 1 shows the comparative relationships between the P-polarized light characteristics, TL, and Rds of Comparative Examples 1 and 2 and Examples 1 to 6.
[0254] Table 1 shows the P-polarized light characteristics, TL, and Rds (%) of Comparative Examples 1-2 and Examples 1-6.
[0255] [Table 1]
[0256] From Table 1, we can see the following:
[0257] (1) The polarization range of the laminated glass P in Comparative Example 1 and Comparative Example 2 is >5%, and it is not smooth. Even if both range1 and range2 are smooth, for example, as in Comparative Example 2, there is a possibility that TL is <70%, which does not meet the automotive safety glass standard.
[0258] (2) Compared with Comparative Example 1 and Comparative Example 2, Examples 1 to 6 have a high Rp, Rp>18%, even Rp>20%, and a small range, the range being <2%, even ≦1%. On the other hand, the present application does not have a high requirement for the range of the reflection spectrum by P-polarized light on one side, and even if the range of the reflection spectrum by P-polarized light on one side reaches 10% or more, a small range (<2%) can be realized by adjusting the second transparent nanofilm. Examples 1 to 5 have R1p>8%, which contributes to the realization of a high Rp. Examples 1 to 6 also have a high visible light transmittance TL≧70%, which meets the TL requirements of automobile windshields.
[0259] Table 2 shows the results of comparing the visible light characteristics (measured from the outer glass substrate side) between Comparative Examples 1 and 2 and Examples 1 to 6.
[0260] Table 2 shows the visible light characteristics (measured from the outer glass substrate side) of Comparative Examples 1 to 2 and Examples 1 to 6.
[0261] [Table 2]
[0262] Table 3 shows the comparison results of the visible light characteristics (measured from the inner glass substrate side) between Comparative Examples 1 and 2 and Examples 1 to 6.
[0263] Table 3 shows the visible light characteristics (measured from the inner glass substrate side) of Comparative Examples 1 to 2 and Examples 1 to 6.
[0264] [Table 3]
[0265] As can be seen from Tables 2 and 3, in Comparative Examples 1 and 2, at a certain angle on the inner glass side, the b value of Comparative Example 1 tends to be negative, resulting in a bluish tint, while at a certain angle in Comparative Example 2, the a value tends to be positive, resulting in a reddish tint, and at the same time the b value also tends to be negative. Examples 1 to 6 all have a good appearance within the incident angle range of 0 to 70°, including measurements from the inner glass substrate side and the outer glass substrate side.
[0266] The above-mentioned examples of the present application only describe the structural composition of the head-up display system, and do not describe the specific layer deposition processes and parameters, and the specific manufacturing processes and parameters of the laminated glass products. It is understood that the undescribed parts are all well known to those skilled in the art, and thus the undescribed parts do not affect the scope of protection of the present application.
[0267] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments may be referred to each other, and each embodiment is described with emphasis on the differences from other embodiments. In the description of this specification, the description referring to the terms "one embodiment", "several embodiments", "examples", "specific examples", or "several examples" means that the specific features, structures, materials, or advantages described with reference to the embodiment or example are included in at least one embodiment or example of the embodiment of this specification. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. And, the specific features, structures, materials, or advantages described may be appropriately combined in any one or more embodiments or examples. Furthermore, unless mutually inconsistent, a person skilled in the art may combine or combine different embodiments or examples and features of different embodiments or examples that appear in this specification.
[0268] The above is merely an example of the embodiment of the present specification, and is not intended to limit the embodiment of the present specification. For those skilled in the art, the embodiment of the present specification may be modified or changed in various ways. It should be understood that any amendments, equivalent replacements, improvements, etc. made within the spirit and principle of the embodiment of the present specification are included in the scope of protection of the embodiment of the present specification.
Claims
1. A laminated glass comprising an inner glass substrate, an outer glass substrate, and an intermediate film interposed between the inner glass substrate and the outer glass substrate, wherein a first transparent nanofilm for reflecting P-polarized light is provided on one side of the inner glass substrate away from the intermediate film, the first transparent nanofilm including at least one laminated structure including a high refractive index material layer and a low refractive index material layer deposited in that order from a surface of the inner glass substrate outward, A second transparent nanofilm is interposed between the inner glass substrate and the outer glass substrate and is adhered to the intermediate film, the second transparent nanofilm includes a dielectric layer and a conductive layer, and each of the conductive layers is interposed between two of the dielectric layers; the high refractive index material layer has a refractive index of 1.9 or more, the low refractive index material layer has a refractive index of 1.8 or less, and the laminated glass has a P-polarized light reflectance Rp≧16% when the incident angle is 65°; The laminated glass is characterized by the above.
2. The laminated glass has a reflection spectrum corresponding to a P-polarized light reflectance Rp in a wavelength band of 460 nm to 630 nm when the incident angle is 65°. The laminated glass according to claim 1 .
3. The solar direct reflectance Rds of the laminated glass is ≧20%. The laminated glass according to claim 1 .
4. The first transparent nanofilm has a one-sided P-polarized light reflectance R1p≧6% when the incident angle is 65°; The laminated glass according to claim 1 .
5. At least one of the high refractive index material layers has a thickness of 45 nm or more and a refractive index of 2.4 or more. The laminated glass according to claim 1 .
6. In the laminated glass, when the incident angle is 65°, the range of the reflection spectrum corresponding to the P-polarized light reflectance Rp in the wavelength band of 460 nm to 630 nm is 4% or less. The laminated glass according to claim 2 .
7. The first transparent nanofilm has a P-polarized light reflectance R1p on one side when the incident angle is 65°, and the range of the reflection spectrum of the P-polarized light in the wavelength band of 460 to 630 nm is defined as range 1; When the incident angle of the second transparent nanofilm is 65°, the range of the reflection spectrum of P-polarized light corresponding to the P-polarized light reflectance R2p of one side in the wavelength band of 460 to 630 nm is range 2. |range1+range2|≦6%, The laminated glass according to claim 1 .
8. The first transparent nanofilm has a P-polarized light reflectance R1p of one side, and a range of range1≦12% in the wavelength band of 460 to 630 nm of the reflection spectrum of the P-polarized light, when the incident angle is 65°; The laminated glass according to claim 1 or 7,
9. The second transparent nanofilm has a P-polarized light reflectance R2p of one side of the reflection spectrum of the P-polarized light in the wavelength band of 460 to 630 nm, and the range 2 is ≦8% when the incident angle is 65°; The laminated glass according to claim 1 or 7,
10. The high refractive index material layer includes a first compound, and the first compound includes at least one of an oxide of Ti, an oxynitride of Ti, a nitride of Ti, and a Ti metal. The laminated glass according to claim 1 .
11. The oxide of Ti contains a first metal element and / or a compound of the first metal element, The first metal element includes at least one of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and a rare earth element; The mass ratio of the first metal element in the Ti oxide is 40% or less. The laminated glass according to claim 10 .
12. The Ti oxynitride contains a second metal element and / or a compound of the second metal element, The second metal element includes at least one of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and a rare earth element; The mass ratio of the second metal element in the Ti oxynitride is 40% or less. The laminated glass according to claim 10 .
13. The low refractive index material layer includes a second compound, and the second compound includes at least one of an oxide of Si, an oxynitride of Si, a carbonate of Si, an oxide of Al, and a Si mixture. The laminated glass according to claim 1 .
14. the oxide of Si, the oxynitride of Si, or the carbonate of Si contains a third metal element and / or a compound of the third metal element; The third metal element includes at least one of Zr, Nb, Ti, Sb, Sn, Zn, In, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and a rare earth element; The mass ratio of the third metal element in the oxide of Si is 30% or less. The laminated glass according to claim 13 .
15. The first transparent nanofilm includes a first high refractive index material layer and a first low refractive index material layer; the thickness of the first high refractive index material layer is between 45 nm and 120 nm; The thickness of the first low refractive index material layer is between 90 nm and 200 nm; The laminated glass according to claim 1 .
16. The first transparent nanofilm includes a first high refractive index material layer, a first low refractive index material layer, a second high refractive index material layer, and a second low refractive index material layer, which are arranged in order; the first high refractive index material layer has a thickness between 1 nm and 60 nm, the second high refractive index material layer has a thickness between 45 nm and 80 nm, The thickness of the first low refractive index material layer is between 1 nm and 200 nm, and the thickness of the second low refractive index material layer is between 90 nm and 200 nm. The laminated glass according to claim 1 .
17. The first transparent nanofilm includes a first high refractive index material layer, a first low refractive index material layer, a second high refractive index material layer, a second low refractive index material layer, a third high refractive index material layer, and a third low refractive index material layer, which are arranged in order; At least one of the first high refractive index material layer, the second high refractive index material layer, and the third high refractive index material layer has a thickness between 45 nm and 80 nm; At least one of the first low refractive index material layer, the second low refractive index material layer, and the third low refractive index material layer has a thickness between 90 nm and 200 nm; The laminated glass according to claim 1 .
18. the first transparent nanofilm comprises a metal layer; The metal layer includes at least one element selected from the group consisting of Ti, Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, Fe, and rare earth elements; The laminated glass according to claim 1 .
19. the first transparent nanofilm comprises a non-stoichiometric metal compound; The non-stoichiometric metal compound comprises at least one element selected from the group consisting of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, Fe, and rare earth elements; The laminated glass according to claim 1 .
20. The high refractive index material layer and / or the low refractive index material layer are provided with a sub-layer. The laminated glass according to claim 1 .
21. The first transparent nanofilm is provided with an improvement layer for improving the performance of the first transparent nanofilm; The improvement layer includes at least one of a high refractive index material layer, a hydrophobic material layer, and a hydrophilic material layer. The laminated glass according to claim 1 .
22. The thickness of the improvement layer is 20 nm or less.
22. The laminated glass according to claim 21 .
23. The conductive layer includes at least one layer having a thickness of 8 nm or less. The laminated glass according to claim 1 .
24. The second transparent nanofilm includes a first dielectric layer, a first conductive layer, and a second dielectric layer, which are disposed in sequence; The first dielectric layer has a thickness of 40 nm or more, and the second dielectric layer has a thickness of 50 nm or more; The thickness of the first conductive layer is between 2 nm and 8 nm. The laminated glass according to claim 1 .
25. The second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, and a third dielectric layer, which are arranged in sequence; the first dielectric layer has a thickness of 25 nm or more, the second dielectric layer has a thickness of 60 nm or more, and the third dielectric layer has a thickness of 40 nm or more; The thickness of the first conductive layer and / or the second conductive layer is 8.0 nm or less; The laminated glass according to claim 1 .
26. The second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, a third dielectric layer, a third conductive layer, and a fourth dielectric layer, which are arranged in sequence; the first dielectric layer has a thickness of 25 nm or more, the second dielectric layer has a thickness of 60 nm or more, the third dielectric layer has a thickness of 50 nm or more, and the fourth dielectric layer has a thickness of 30 nm or more; the first conductive layer has a thickness between 5 nm and 12 nm, and the second conductive layer and the third conductive layer each have a thickness between 2 nm and 8 nm; The laminated glass according to claim 1 .
27. The second transparent nanofilm includes a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, a third dielectric layer, a third conductive layer, a fourth dielectric layer, a fourth conductive layer, and a fifth dielectric layer, which are arranged in sequence; the first conductive layer, the second conductive layer, the third conductive layer, and the fourth conductive layer each have a thickness of 8 nm or less; The laminated glass according to claim 1 .
28. The second transparent nanofilm includes, in order, a first dielectric layer, a first conductive layer, a second dielectric layer, a second conductive layer, a third dielectric layer, a third conductive layer, a fourth dielectric layer, a fourth conductive layer, a fifth dielectric layer, a fifth conductive layer, and a sixth dielectric layer; the first conductive layer, the second conductive layer, the third conductive layer, the fourth conductive layer, and the fifth conductive layer each have a thickness of 8 nm or less; The laminated glass according to claim 1 .
29. The conductive layer contains at least one element selected from the group consisting of Ag, Ni, Cr, Cu, Fe, Mn, Pt, Ti, Zn, Sn, Al, Si, and rare earth elements. The laminated glass according to claim 1 .
30. The conductive layer and / or the dielectric layer includes a sub-layer. The laminated glass according to claim 1 .
31. At least one of the dielectric layers contains Zn and Sn, The atomic ratio of Zn to Sn is between 0.4 and 0.
6. The laminated glass according to claim 1 .
32. the dielectric layer includes a first functional layer and a second functional layer; the first functional layer is used to reduce or prevent the conductive layer from chemically reacting in air and / or during heat treatment; The second functional layer is used to reduce or prevent chemical reaction of the conductive layer during plating of a film, The first functional layer contains at least one element selected from the group consisting of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, Ta, and rare earth elements; The second functional layer includes a compound of at least one element selected from the group consisting of Zn, Sn, Ga, Al, F, In, V, Li, K, Nb, and Ti, or a mixed compound of at least one element selected from the group consisting of Zn, Sn, Ga, Al, F, In, V, Li, K, Nb, and Ti; The laminated glass according to claim 1 .
33. The laminated glass has a value a in the red-green direction of reflected color of visible light within an incident angle range of 0° to 60°, the value being in the range of −10≦a≦4; The laminated glass has a b value in the yellow-blue direction in the reflected color of visible light within an incident angle range of 0° to 60°, which is in the range of −10≦b≦4. The laminated glass according to claim 1 .
34. The laminated glass has a value a in the red-green direction of reflected color of visible light within an incident angle range of 45° to 75°, the value being in the range of −10≦a≦4; The laminated glass has a b value in the yellow-blue direction in the reflected color of visible light within an incident angle range of 45° to 75°, which is in the range of −10≦b≦4. The laminated glass according to claim 1 .
35. A projection system comprising the laminated glass according to any one of claims 1 to 34. A head-up display system comprising:
36. a dominant wavelength of the projection system is 460 nm or greater; 36. A head-up display system as claimed in claim 35.
Citation Information
Patent Citations
Head-up display sandwich glass with electric heating function
CN106630688A
Head-up display laminated glass capable of realizing thermal insulation function
CN106646874A
Head-up display glass and head-up display system
CN113071165A
Head-up display system
CN113238378A
Projection arrangement for a head-up display (HUD) with p-polarised radiation
US20210316533A1